”Analisis Pengaruh Manajemen Persediaan terhadap Efektivitas Pengelolaan kas pada Perusahaan Manufaktur CV. X” - Desty Natalia Puspaningrum; Fitri Komariyah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the effect of inventory management on the effectiveness of cash management in manufacturing companies. The main issue faced by CV. X is the high amount of capital tied up in inventory, resulting in liquidity difficulties despite stable sales. The research applies a descriptive quantitative method, using financial report documentation and interviews as data collection techniques. The findings indicate that ineffective inventory management directly impacts the company’s cash flow capability. Inaccurate inventory records also lead to poor decision-making in raw material procurement. Therefore, the implementation of stock cards and regular inventory control is highly recommended to maintain a balance between stock availability and operational needs.